Chinese Law Through the Eyes of Foreign Missionaries: Focusing on The Chinese Recorder - YANG, Yuna (Journal of Research for Christianity in China (JRCC), 2025)
The Chinese Recorder preserves a wealth of articles concerning Republican-era law, serving as valuable material for studying the evolution of missionaries' understanding of Chinese legislation. In their interpretations and evaluations of late Qing and Republican legal systems, missionaries emphasized the continuity between ancient and modern legal principles while prioritizing the development of modern law. Their legal perspectives were more objective compared to those of 19th-century missionaries. Regarding church affairs and law, they sought to leverage unequal treaties signed between their home countries and China to secure privileges while simultaneously hoping their governments would refrain from excessive interference in missionary activities. As anti-imperialist movements surged among the populace in the 20th century and governments gradually reclaimed these privileges, this contradictory mindset and predicament rendered missionary work increasingly complex.